2005
DOI: 10.1007/s00402-005-0807-5
|View full text |Cite
|
Sign up to set email alerts
|

Radiation exposure to the hands of orthopaedic surgeons: are we underestimating the risk?

Abstract: The risk of radiation exposure appears to be higher than previously reported. Fingertips are more susceptible to radiation exposure and should therefore be monitored in forthcoming studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
52
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(54 citation statements)
references
References 18 publications
1
52
0
1
Order By: Relevance
“…A similar relation between experience and radiation exposure was also found in other studies [61][62][63].…”
Section: Surgeries At Hip Femur and Tibiasupporting
confidence: 84%
“…A similar relation between experience and radiation exposure was also found in other studies [61][62][63].…”
Section: Surgeries At Hip Femur and Tibiasupporting
confidence: 84%
“…[3][4][5][6][7][8][9][10][11][12][13] While the majority of current research into the safety of fluoroscopy has involved cardiac catheterization procedures, various papers have also addressed the safety of fluoroscopically-guided spinal surgery. 3,4,[7][8][9]11,12 Jones et al 3 found the radiation exposure to the physician during lumbar pedicle screw insertion to be measurable yet still less than 10% of recommended limits for the hand, thyroid, and eyes.…”
mentioning
confidence: 99%
“…Hafiz et al, reported that the orthopedic surgeon finger may exposed to exposure to the primary beam during surgical protocols. Although surgeons and members of surgical teams are aware that their hands should never be exposed to primary radiation, it is not unusual for fingers to be accidentally caught in the beam (Hafez et al, 2005). Although, it is well known that wearing protective shields will reduce the radiation dose, the orthopedic surgeons as well as other operators believe that the use of lead glasses impairs vision and so increases the exposure time and that lead gloves are inconvenient.…”
Section: Discussionmentioning
confidence: 97%